2002
DOI: 10.2172/1875862
|View full text |Cite
|
Sign up to set email alerts
|

Letter of Intent to build an Off-axis Detector to study $\nu_{\mu} → \nu _e$ oscillations with NuMI Neutrino Beam

Abstract: Motivation 2 The Role of the MINOS 3 Possible Evolution of Neutrino Physics 4 Off-Axis NuMI Neutrino Beam 4.1 NuMI Off-Axis Neutrino Fluxes 4.2 4.3 Antineutrino Beams 4.4 Proton Economics 5 v/1 5.1 5.2 Possible 5.3 Background measurements and estimates; 5.4 Physics Potential of the NuMI Off-axis Beam 5.5 with JHF Phase I . . . . Future Evolution of the Off-Axis Neutrino '-'~.~~•.~

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 0 publications
1
41
0
1
Order By: Relevance
“…We demonstrated that the study of exclusive channels like D or D * charmed meson production are very complementary to the hadronic program of electron facilities such as JLab, by giving access to elusive quantities like the quark or gluon transversity GPDS. We believe that planned high energy neutrino experiments such as Minerve and Minos+ [10,11] which have their scientific program oriented toward the understanding of neutrino oscillations will collect more statistics and will thus allow some nice progress in the realm of hadronic physics.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that the study of exclusive channels like D or D * charmed meson production are very complementary to the hadronic program of electron facilities such as JLab, by giving access to elusive quantities like the quark or gluon transversity GPDS. We believe that planned high energy neutrino experiments such as Minerve and Minos+ [10,11] which have their scientific program oriented toward the understanding of neutrino oscillations will collect more statistics and will thus allow some nice progress in the realm of hadronic physics.…”
Section: Discussionmentioning
confidence: 99%
“…We have selected the two most common neutrino event generators: Generates Events for Neutrino Interaction Experiments (GENIE) v-3.0.6 [18] and NuWro [19] version 19.01 to perform our studies that are currently being used by most of the neutrino experiments in the USA and other coun- tries. GENIE is being used by many neutrino baseline experiments running around the world, such as Minerva [20], MINOS [21], MicroBooNE [14], NOvA [22], and ArgoNEUT [23] experiments. NuWro has been developed by a group of physicists Cezary Juszczak et al at the Wroclaw University [19] and is now being used as a complementary neutrino events generator by most neutrino experiments.…”
Section: Event Generators: Genie and Nuwromentioning
confidence: 99%
“…Calorimeters measure the visible energy deposited by the final-state particles associated with each event. They were used in MINOS [39] and NOvA [40] experiments. In these experiments, the total energy deposited by all reaction products is measured without a prior reconstruction of the track, momentum, or energy of each final-state particle.…”
Section: Energy Reconstructionmentioning
confidence: 99%